Evaluating serum bilirubin levels in acute appendicitis and appendiceal perforation - Bali, Rajandeep Singh; ., Rajni; Watali, Yawar; Gupta, Shyam Kumar; Gupta, Geetanjali (International Journal of Research in Medical Sciences, 2020)
Background: Acute appendicitis is one of the commonest surgical emergencies. Authors undertook this study to evaluate serum bilirubin levels in acute appendicitis and appendiceal perforation. Methods: A retrospective study evaluating the serum bilirubin levels in acute appendicitis and appendiceal perforation was carried out for 6 years at three tertiary care hospitals at India from 2014 to 2019. Patients having acute appendicitis and appendiceal perforation, confirmed on histopathology, with no other medical or surgical comorbidity were included in the study. Results: The total number of our study subjects was 927. 306 patients had appendiceal perforation, amongst these, 226 (74%) had hyperbilirubinemia. Out of the 621 patients having acute appendicitis only 186 (30%) had hyperbilirubinemia. The lowest and the highest serum bilirubin levels of this study group were 0.6 and 3.1 mg/dl, respectively, with an average of 1.6 mg/dl. In patients diagnosed to be having acute appendicitis, the lowest and highest serum bilirubin levels were 0.6 and 2.4 mg/dl, respectively, with an average of 1.3 mg/dl. As for the patients having appendiceal perforation the lowest and highest serum bilirubin levels were 0.8 and 3.1 mg/dl, respectively, with an average of 1.8 mg/dl. Conclusions: Hyperbilirubinemia is seen in acute appendicitis but predominantly in appendiceal perforation, so serum bilirubin estimation may help us in diagnosing appendiceal perforation pre-operatively if and when used in conjunction with other available diagnostic modalities.